Optimal design of double‐skin façades as vibration absorbers. Issue 2 (25th August 2017) - Pipitone, Giovanni; Barone, Giorgio; Palmeri, Alessandro
Summary: In this paper, several layouts of double‐skin façades (DSFs) used as mass dampers to reduce the vibrations in structures under seismic events are analyzed. First, the mathematical coupled problem is studied considering a non‐classically damped system excited by a set of accelerograms. The design problem aims to determine the optimal values of four parameters, namely, the flexural stiffness and damping of the DSF panel and the stiffnesses of the elements that connect the DSF to the primary structure. Second, four objective functions are investigated. Two of these functions aim to minimise, respectively, the variance of displacements and accelerations of the primary structure for each earthquake record. The remaining two, instead, minimise the average of the displacements and accelerations calculated for all the selected accelerograms. Finally, numerical analyses are performed on a 6‐storey building and four DSF designs are proposed. The particle swarm optimisation is used to estimate the optimal parameters. Comparisons among the DSF layouts are presented in terms of minima of the objective functions and in terms of energy transfer functions, and a simplified design method for the connection elements is discussed.